A method for preparing ultraviolet light-cured water-based coating

By performing prepolymerization and polycondensation reaction under high temperature and high pressure environment and combining photoinitiators, low-pollution, high-performance ultraviolet cured water-based coatings are prepared, which solves the problem of environmental pollution and dependence on fossil raw materials of solvent-based coatings, and achieves green An alternative to renewable resources, improving the mechanical properties and hydrophobic oleophobic effects of the coating.

CN118389035BActive Publication Date: 2025-01-10NINGBO CAIGE NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410672612.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-01-10
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

The existing ultraviolet curing coatings are mainly solvent-based, with high VOC content, which leads to environmental pollution, and rely on fossil raw materials, lacking alternatives to green renewable resources.

Method used

Itaconic acid, tartaric acid, polyol, catalyst and polymerization inhibitor are used to carry out prepolymerization and polycondensation reaction under high temperature and high pressure environments, combined with photoinitiators, ultraviolet cured water-based coatings are prepared, and renewable bio-based materials are used to combine with water-based Technology and UV curing technology form low-pollution and high-performance coatings.

Benefits of technology

Low-pollution, high-performance ultraviolet cured water-based coatings are achieved, which improves the hardness, impact resistance and flexibility of the coating. The hydrophobic oleophobic properties are improved through modified silicon carbide spraying, replacing traditional solvent-based coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004863110020000061
    Figure BDA0004863110020000061
  • Figure BDA0004863110020000071
    Figure BDA0004863110020000071
  • Figure BDA0004863110020000072
    Figure BDA0004863110020000072
Patent Text Reader

Abstract

The present application relates to the technical field of water-based coatings, and more specifically, it relates to a method for preparing a UV-curable water-based coating. A method for preparing a UV-curable water-based coating comprises the following steps: S1, firstly, itaconic acid, tartaric acid, polyols, catalyst p-toluenesulfonic acid and inhibitor p-hydroxyanisole are mixed, and then reacted at a temperature of 150°C in a nitrogen atmosphere to obtain a prepolymerization reaction liquid; the polyol is a mixture of one or two of castor oil and isosorbide; S2, the polycondensation catalyst dibutyltin dilaurate is added to the prepolymerization reaction liquid, and vacuum reacted at 150°C to obtain an itaconic acid-based unsaturated polyester; S3, the itaconic acid-based unsaturated polyester is mixed with deionized water, then stirred and warmed to 40-60°C and triethylamine is added dropwise, and then a photoinitiator is added to continue stirring to obtain a UV-curable water-based coating. The UV-curable water-based coating of the present application has excellent strength, toughness, pollution-free and green environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of water-based coatings, and more specifically, to a method for preparing a UV-curable water-based coating. Background Art

[0002] UV-curing coatings refer to coatings that, under UV irradiation, the photoinitiator in the coating absorbs UV radiation energy and then splits into free radicals. The outer electrons of the molecules jump, generating active centers in a very short time. The active centers then react with the unsaturated groups in the resin, causing the double bonds in the photocurable resin and active diluent molecules to break, triggering polymerization, cross-linking, and grafting reactions in the prepolymer, which cures into a network polymer in a very short time.

[0003] UV-curable coatings transform from liquid to solid within seconds to form a film-forming substance. They cure quickly, and the cured coating has high hardness, good wear resistance, and low energy consumption, so they are widely used. However, conventional UV-curable coatings are basically solvent-based UV-curable coatings, which have a high VOC content and are prone to environmental pollution. In addition, the polymer industry is heavily dependent on fossil raw materials, so there is an urgent need for a coating that uses green renewable resources as raw materials and combines water-based technology and UV-curing technology to replace traditional solvent-based coatings. Summary of the invention

[0004] In order to improve the defects of conventional solvent-based coatings such as high pollution and environmental pollution, the present application provides a method for preparing ultraviolet light-cured water-based coatings.

[0005] The present application provides a method for preparing a UV-curable water-based coating, which adopts the following technical solution:

[0006] A method for preparing a UV-curable water-based coating comprises the following steps:

[0007] S1. First, itaconic acid, tartaric acid, polyol, p-toluenesulfonic acid as a catalyst and p-hydroxyanisole as an inhibitor are mixed, and then the temperature is raised to 140-160° C. under a nitrogen atmosphere, and the mixture is stirred at a constant temperature until the acid value remains unchanged to obtain a prepolymerization reaction liquid;

[0008] The polyol is one or a mixture of castor oil and isosorbide;

[0009] S2, adding a polycondensation catalyst dibutyltin dilaurate to the prepolymerization reaction liquid, then controlling the vacuum degree to 0.09-0.1 MPa, reacting at a constant temperature of 140-160° C. until the acid value remains unchanged, and then cooling to obtain an itaconic acid-based unsaturated polyester;

[0010] S3. Mix the itaconic acid-based unsaturated polyester with deionized water, then stir and heat to 40-60°C and drop triethylamine, then adjust to neutral and add deionized water to a solid content of 80%, stir at a constant temperature for 1-2 hours, then add a photoinitiator and continue stirring to obtain a UV-curable water-based coating.

[0011] Itaconic acid contains a carbon-carbon double bond and two carboxyl groups in its molecular structure, tartaric acid is a bio-based monomer containing two carboxyl groups and two hydroxyl groups, isosorbide is a solid diol containing a bicyclic rigid structure, and castor oil contains polyhydroxyl functional groups of long-chain non-polar fatty acid chains. Therefore, under the conditions of catalyst, polymerization inhibitor, high temperature and high pressure, the four monomers can undergo prepolymerization and polycondensation, and then with the addition of a photoinitiator, a UV-curable water-based coating can be obtained. The above-mentioned UV-curable water-based coating uses renewable bio-based materials, combined with water-based technology and UV-curing technology, and has the advantages of low pollution, good performance and renewability.

[0012] Preferably, the polyol is a mixture of castor oil and isosorbide.

[0013] Isosorbide contains a bicyclic rigid structure, so the addition of isosorbide can effectively improve the hardness and impact resistance of UV-curable waterborne coatings, but it can also lead to insufficient flexibility and brittleness of UV-curable waterborne coatings. When isosorbide is added in combination with castor oil, the long-chain non-polar fatty acid chain and polyhydroxy structure of castor oil itself can form a three-dimensional cross-linked network, thereby improving the flexibility of UV-curable waterborne coatings. In addition, the lack of dispersibility caused by the long-chain non-polar fatty acid chain of castor oil itself can be compensated by the high polarity of tartaric acid.

[0014] In summary, compared with using castor oil or isosorbide alone, when the polyol is a mixture of castor oil and isosorbide, the prepared UV-curable water-based coating will have more balanced strength and toughness.

[0015] Preferably, the molar ratio of itaconic acid, tartaric acid, castor oil and isosorbide is (9-10):(2-3):(5-7):(3-5).

[0016] When itaconic acid, tartaric acid, castor oil and isosorbide are used in the above molar ratio, the prepared UV-curable water-based coating will have more balanced strength, toughness and dispersibility.

[0017] Preferably, the photoinitiator is a mixture of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and dicyclopentadienyl iron.

[0018] Dicyclopentadienyl iron has electron-absorbing property, so when dicyclopentadienyl iron is used in combination with 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, dicyclopentadienyl iron and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone can undergo nucleophilic substitution reaction, thereby reducing the electron cloud density of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and promoting 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone to show better activity.

[0019] Moreover, dicyclopentadienyl iron can form Lewis acid under ultraviolet radiation, thereby forming empty orbitals and initiating the activity of cationic polymerization, extending the light absorption region, and improving the activity of the photoinitiator.

[0020] Specifically, the curing speed of UV-curable water-based coatings is accelerated, the curing effect is better, and the strength and toughness of UV-curable water-based coatings are improved.

[0021] Preferably, the mass ratio of the 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone to dicyclopentadienyl iron is (6-10):1.

[0022] When 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and dicyclopentadienyl iron are in the above mass ratio, the prepared UV-curable water-based coating will have better strength and toughness.

[0023] Preferably, the photoinitiator is added in an amount of 0.8-1.2% of the total mass, the polycondensation catalyst is added in an amount of 0.4-0.6% of the total mass, the catalyst is added in an amount of 0.4-0.6% of the total mass, and the inhibitor is added in an amount of 0.4-0.6% of the total mass.

[0024] Preferably, the UV-curable water-based coating coating step is: applying the UV-curable water-based coating to the surface of the workpiece, then placing it in an oven at 50-70°C for 24-36 hours, and then curing it with a UV curing machine to obtain a UV-curable water-based coating.

[0025] Preferably, after the UV-curable water-based coating is applied to the surface of the workpiece, the modified silicon carbide is first sprayed on the surface of the UV-curable water-based coating, and then placed in an oven at 50-70° C. for 24-36 hours.

[0026] Preferably, the preparation method of the modified silicon carbide comprises the following steps:

[0027] S1. First, heptadecafluorodecyltrimethoxysilane and ethanol are mixed, wherein the content of heptadecafluorodecyltrimethoxysilane is 10%, to obtain a modified solution;

[0028] S2. Soak the nano-silicon carbide in the modification liquid for 1-3 hours, and then place it in an oven at 50-70° C. for drying, and then add it to 3-(amino)propyltriethoxysilane and mix well to obtain modified silicon carbide.

[0029] UV-curing coatings are usually used for surface protection of home furniture. During the use of furniture, water or oil stains are easily attached to the coating surface. As time goes by, the water or oil stains will be extremely difficult to remove, thus affecting the appearance of the home.

[0030] After the modified silicon carbide is sprayed on the surface of the UV-curable water-based coating, the silicon carbide will form a convex micro-nano structure, which increases the roughness of the coating and is conducive to the super-hydrophobic and high-oleophobic effects of the coating. The pre-treatment of heptadecafluorodecyltrimethoxysilane will make the water and oil have a lower surface energy, thus having a better hydrophobic and oleophobic effect.

[0031] 3-(Amino)propyltriethoxysilane forms hydrogen bonds with the hydroxyl groups on the surface of silicon carbide and the hydroxyl groups in the UV-curable water-based coating through its amine group, generating a force that makes the connection between the modified silicon carbide and the UV-curable water-based coating more stable and firm.

[0032] In summary, this application has the following beneficial effects:

[0033] 1. The molecular structure of itaconic acid contains a carbon-carbon double bond and two carboxyl groups, tartaric acid is a bio-based monomer containing two carboxyl groups and two hydroxyl groups, isosorbide is a solid diol containing a bicyclic rigid structure, and castor oil contains polyhydroxyl functional groups of long-chain non-polar fatty acid chains. Therefore, under the conditions of catalyst, inhibitor, high temperature and high pressure, the four monomers can undergo prepolymerization and polycondensation, and then with the addition of a photoinitiator, a UV-curable water-based coating can be obtained. The above-mentioned UV-curable water-based coating uses renewable bio-based materials, combines water-based technology and UV-curing technology, and has the advantages of low pollution, good performance and renewability.

[0034] 2. When isosorbide is added in combination with castor oil, isosorbide can effectively improve the hardness and impact resistance of UV-curable water-based coatings. The long-chain non-polar fatty acid chain and polyhydroxy structure of castor oil itself can form a three-dimensional cross-linked network, thereby improving the flexibility of UV-curable water-based coatings. In addition, the lack of dispersibility caused by the long-chain non-polar fatty acid chain of castor oil itself can be compensated by the high polarity of tartaric acid.

[0035] 3. Dicyclopentadiene iron can accelerate the curing speed of UV-curable water-based coatings, achieve better curing effects, and enhance the strength and toughness of UV-curable water-based coatings. DETAILED DESCRIPTION

[0036] The present application is further described in detail below in combination with application examples 1-11 and application comparative example 1.

[0037] raw material

[0038] Itaconic acid CAS: 97-65-4; Tartaric acid CAS: 526-83-0; p-Toluenesulfonic acid CAS: 104-15-4; p-Hydroxyanisole CAS: 150-76-5; Castor oil CAS: 8001-79-4; Isosorbide CAS: 652-67-5; Dibutyltin dilaurate CAS: 77-58-7; Triethylamine CAS: 121-44-8;

[0039] 2-Hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone CAS: 106797-53-9; Dicyclopentadienyl iron CAS: 102-54-4; Heptadecafluorodecyltrimethoxysilane CAS: 83048-65-1;

[0040] Ethanol CAS: 64-17-5; Nano-silicon carbide 150nm; 3-(Amino)propyltriethoxysilane CAS: 919-30-2.

[0041] Example

[0042] Example 1

[0043] A method for preparing a UV-curable water-based coating comprises the following steps:

[0044] S1, firstly, itaconic acid, tartaric acid, castor oil, a catalyst of p-toluenesulfonic acid and a polymerization inhibitor of p-hydroxyanisole are mixed, then the temperature is raised to 150° C. under a nitrogen atmosphere, and the mixture is stirred at a constant temperature to react until the acid value remains unchanged, thereby obtaining a prepolymerization reaction liquid;

[0045] The mass ratio of itaconic acid, tartaric acid and castor oil is 19:5:20, the amount of catalyst added is 0.5% of the total mass, and the amount of inhibitor added is 0.5% of the total mass;

[0046] S2, adding a polycondensation catalyst dibutyltin dilaurate to the prepolymerization reaction liquid, the amount of the polycondensation catalyst added is 0.5% of the total mass, then controlling the vacuum degree to 0.1 MPa, reacting at a constant temperature of 150° C. until the acid value remains unchanged, and then cooling to obtain an itaconic acid-based unsaturated polyester;

[0047] S3. Mix the itaconic acid-based unsaturated polyester with an equal amount of deionized water, then stir and heat to 50°C and add 1% of the total mass of triethylamine, then adjust to neutral and add deionized water to a solid content of 80%, stir at a constant temperature for 1.5 hours, then add a photoinitiator 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and continue stirring, the amount of photoinitiator added is 1% of the total mass, and a UV-curable water-based coating is obtained.

[0048] Example 2

[0049] The difference from Example 1 is that castor oil is replaced with isosorbide in the same amount.

[0050] Example 3

[0051] The difference from Example 1 is that castor oil is replaced by a mixture of castor oil and isosorbide with the same added amount, and the molar ratio of itaconic acid, tartaric acid, castor oil and isosorbide is 19:5:12:8.

[0052] Embodiment 4-7

[0053] The difference from Example 3 is that the molar ratios of itaconic acid, tartaric acid, castor oil and isosorbide are different, as shown in Table 1.

[0054] Table 1 Molar ratio of each component of UV-curable waterborne coating in Examples 3-7

[0055]

[0056]

[0057] Example 8

[0058] The difference from Example 3 is that the photoinitiator is 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and dicyclopentadienyl iron in a mass ratio of 8:1.

[0059] Examples 9-10

[0060] The difference from Example 8 is that the mass ratio of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone to dicyclopentadienyl iron is different, as shown in Table 2.

[0061] Table 2 Mass ratio of each component of the photoinitiator in Examples 8-10

[0062]

[0063] Comparative Example

[0064] Comparative Example 1 is a UV-curable water-based coating, which is SJ-8026.

[0065] Application Examples

[0066] Application Examples 1-10

[0067] A coating method of an ultraviolet light-cured water-based coating, comprising the steps of: coating Examples 1-10 on a workpiece surface with a coating thickness of 50 μm, then placing the workpiece in an oven at 60° C. for 30 hours, and then curing the workpiece with an ultraviolet light curing machine (300 nm, Dongguan Yiheng Instrument Technology Co., Ltd.) to obtain an ultraviolet light-cured water-based coating.

[0068] Application Example 11

[0069] The difference from Application Example 8 is that after the UV-curable water-based coating is applied to the surface of the workpiece, the modified silicon carbide is first sprayed on the surface of the UV-curable water-based coating, and the spraying amount is 10% of the total mass, and then placed in an oven;

[0070] The preparation method of modified silicon carbide comprises the following steps:

[0071] S1. First, heptadecafluorodecyltrimethoxysilane and ethanol are mixed, wherein the content of heptadecafluorodecyltrimethoxysilane is 10%, to obtain a modified solution;

[0072] S2. Soak the nano-silicon carbide in the modified liquid for 2 hours, then place it in an oven at 60°C for drying, and then add it to 3-(amino)propyltriethoxysilane and mix evenly. The mass ratio of 3-(amino)propyltriethoxysilane to nano-silicon carbide is 3:1 to obtain modified silicon carbide.

[0073] Application Example 12

[0074] The difference from Application Example 11 is that no 3-(amino)propyltriethoxysilane is added.

[0075] Application comparison

[0076] Application Comparative Example 1

[0077] A coating method of an ultraviolet light-cured water-based coating, comprising the following steps: coating comparative example 1 on a workpiece surface with a coating thickness of 50 μm, subsequently placing the workpiece in an oven at 60° C. for 30 hours, and then curing the workpiece with an ultraviolet light curing machine (300 nm, Dongguan Yiheng Instrument Technology Co., Ltd.) to obtain an ultraviolet light-cured water-based coating.

[0078] Performance testing

[0079] Detection Methods

[0080] 1. Coating hardness test

[0081] Three samples were taken from application examples 1-10 and application comparative example 1, and then the hardness of the cured coating was tested with a Zhonghua pencil and a pencil hardness tester BGD 506 / 2 according to GB / T6739-2006, and the average value was taken to one decimal place. The test data are shown in Table 3.

[0082] 2. Coating toughness test

[0083] Three samples were taken from application examples 1-10 and application comparative example 1, and then the flexibility of the cured coating was measured using a bending tester WQ-Ⅱ with reference to GB / T6742-2007, and the average value was taken to one decimal place. The test data are shown in Table 3.

[0084] 3. Hydrophobic and oleophobic performance test

[0085] Three samples were taken out from Application Example 8 and Application Examples 11-12 respectively, and the mass of the samples was tested and recorded as M0. Then the samples were placed vertically and 100g of oil-water mixture was sprayed on the surface of the samples. The oil-water mixture was obtained by mixing peanut oil and water in a mass ratio of 1:1. After spraying, the samples were allowed to stand for 10 minutes, and then the mass was measured and recorded as M1. Finally, the adhesion value was calculated and the average value was taken. The adhesion value = M1-M0. The test data are shown in Table 4.

[0086] Table 3 Hardness and toughness of application examples 1-10 and comparative example 1

[0087]

[0088] Table 4 Hydrophobic and oleophobic properties of Application Example 8 and Application Examples 11-12

[0089] Application Example 8 Application Example 11 Application Example 12 Adhesion value / g 1.3g 0.7g 0.9g

[0090] With reference to Application Examples 1-3 and Application Comparative Example 1 and in combination with Table 3, it can be seen that among Application Examples 1-3, Application Example 1 has better flexibility, Application Example 2 has better hardness, and Application Example 3 has more balanced hardness and flexibility. In fact, the comprehensive performance of Application Example 3 is similar to that of Application Comparative Example 1, that is, the component ratio of Application Example 3 can replace conventional solvent-based water-based UV-curing coatings.

[0091] Among them, the reason for the excellent flexibility of Application Example 1 is that the long-chain non-polar fatty acid chain and polyhydroxy structure of castor oil itself can form a three-dimensional cross-linked network, thereby improving the flexibility of the UV-curable water-based coating.

[0092] The reason for the excellent hardness of Application Example 2 is that isosorbide contains a bicyclic rigid structure, so the addition of isosorbide can effectively improve the hardness and impact resistance of the UV-curable water-based coating.

[0093] When castor oil and isosorbide are used in combination, the UV-curable water-based coating can complement each other in hardness and toughness, thereby obtaining more balanced mechanical properties.

[0094] Referring to Application Examples 3-7 and in combination with Table 3, it can be seen that Application Examples 4 and Application Examples 7 have better hardness, Application Examples 5-6 have better toughness, but Application Example 3 has more balanced hardness and toughness. That is, when itaconic acid, tartaric acid, castor oil and isosorbide use the molar ratio of Application Example 3, the prepared UV-curable water-based coating will have more balanced mechanical properties.

[0095] With reference to Application Example 3 and Application Example 8 and in combination with Table 3, it can be seen that, relative to Application Example 3, the hardness and flexibility of Application Example 8 are improved to a certain extent, which indicates that the addition of dicyclopentadiene iron can synergistically improve the hardness and toughness of the UV-curable water-based coating.

[0096] The reason is that dicyclopentadienyl iron has electron-absorbing property. Therefore, when dicyclopentadienyl iron is used in combination with 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, dicyclopentadienyl iron and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone can undergo nucleophilic substitution reaction, thereby reducing the electron cloud density of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, and promoting 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone to show better activity. Moreover, dicyclopentadienyl iron can form Lewis acid under ultraviolet radiation, thereby forming empty orbits and initiating the activity of cationic polymerization, extending the light absorption region, and improving the activity of the photoinitiator.

[0097] Specifically, the curing speed of UV-curable water-based coatings is accelerated, the curing effect is better, and the strength and toughness of UV-curable water-based coatings are improved.

[0098] With reference to Application Examples 8-10 and in combination with Table 3, it can be seen that, relative to Application Example 8, the hardness and flexibility of Application Example 9 are basically unchanged, but the flexibility of Application Example 10 is slightly deteriorated. This indicates that when the mass ratio of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and dicyclopentadienyl iron is adopted in Application Example 8, the strength and toughness of the UV-cured water-based coating can reach the best.

[0099] Referring to Application Example 8 and Application Example 11 and in combination with Table 4, it can be seen that the adhesion value of Application Example 11 is significantly reduced compared with Application Example 8, which indicates that the spraying of modified silicon carbide can effectively improve the hydrophobic and oleophobic properties of the UV-cured water-based coating.

[0100] The reason is that silicon carbide will form a convex micro-nano structure, which increases the roughness of the coating, which is beneficial to the super hydrophobic and high oleophobic effects of the coating, while the pre-treatment with heptadecafluorodecyltrimethoxysilane will make water and oil have a lower surface energy, thus having a better hydrophobic and oleophobic effect.

[0101] Referring to Application Example 8 and Application Examples 11-12 and in combination with Table 4, it can be seen that the adhesion value of Application Example 12 is significantly reduced compared with Application Example 8, but the adhesion value of Application Example 12 is relatively high compared with Application Example 11, which shows that the addition of 3-(amino)propyltriethoxysilane can also improve the hydrophobic and oleophobic properties of the UV-cured water-based coating.

[0102] The reason is that 3-(amino)propyltriethoxysilane forms hydrogen bonds with the hydroxyl groups on the surface of silicon carbide and the hydroxyl groups in the UV-curable water-based coating through its amine group, generating a force that makes the connection between the modified silicon carbide and the UV-curable water-based coating more stable and firm, effectively reduces the deviation of the modified silicon carbide, and indirectly improves the hydrophobic and oleophobic properties of the UV-curable water-based coating.

[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a UV-curable water-based coating, characterized in that: The following steps are involved: S1. First, itaconic acid, tartaric acid, polyol, p-toluenesulfonic acid as a catalyst and p-hydroxyanisole as an inhibitor are mixed, and then the temperature is raised to 140-160° C. under a nitrogen atmosphere, and the mixture is stirred at a constant temperature until the acid value remains unchanged to obtain a prepolymerization reaction liquid; The polyol is one or a mixture of castor oil and isosorbide; S2, adding a polycondensation catalyst dibutyltin dilaurate to the prepolymerization reaction liquid, then controlling the vacuum degree to 0.09-0.1 MPa, reacting at a constant temperature of 140-160° C. until the acid value remains unchanged, and then cooling to obtain an itaconic acid-based unsaturated polyester; S3, mixing itaconic acid-based unsaturated polyester with deionized water, then stirring and heating to 40-60° C. and adding triethylamine dropwise, then adjusting to neutral and adding deionized water to a solid content of 80%, stirring at a constant temperature for 1-2 hours, then adding a photoinitiator and continuing to stir to obtain a UV-curable water-based coating; The polyol is a mixture of castor oil and isosorbide, and the molar ratio of itaconic acid, tartaric acid, castor oil and isosorbide is (9-10): (2-3): (5-7): (3-5).

2. The method for preparing the UV-curable water-based coating according to claim 1, characterized in that: The photoinitiator is a mixture of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and dicyclopentadienyl iron.

3. The method for preparing the UV-curable water-based coating according to claim 2, characterized in that: The mass ratio of the 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone to dicyclopentadienyl iron is (6-10):

1.

4. The method for preparing the UV-curable water-based coating according to claim 1, characterized in that: The amount of the photoinitiator added is 0.8-1.2% of the total mass, the amount of the polycondensation catalyst added is 0.4-0.6% of the total mass, the amount of the catalyst added is 0.4-0.6% of the total mass, and the amount of the inhibitor added is 0.4-0.6% of the total mass.

5. The method for preparing the UV-curable water-based coating according to claim 1, characterized in that: The UV-curable water-based coating coating step is: coating the UV-curable water-based coating on the surface of the workpiece, then placing it in an oven at 50-70° C. for 24-36 hours, and then curing it with a UV curing machine to obtain a UV-curable water-based coating.

6. The method for preparing the UV-curable water-based coating according to claim 5, characterized in that: After the UV-curing water-based paint is applied to the surface of the workpiece, the modified silicon carbide is first sprayed on the surface of the UV-curing water-based paint, and then placed in an oven at 50-70°C for 24-36 hours.

7. The method for preparing the UV-curable water-based coating according to claim 6, characterized in that: The preparation method of the modified silicon carbide comprises the following steps: S1. First, heptadecafluorodecyltrimethoxysilane and ethanol are mixed, wherein the content of heptadecafluorodecyltrimethoxysilane is 10%, to obtain a modified solution; S2. Soak the nano-silicon carbide in the modification liquid for 1-3 hours, and then place it in an oven at 50-70° C. for drying, and then add it to 3-(amino)propyltriethoxysilane and mix well to obtain modified silicon carbide.

Citation Information

Patent Citations

  • Ultraviolet curing itaconic acid-based polyester resin and preparation method thereof

    CN113667106A

  • Water-based bio-based coating as well as preparation method and application thereof

    CN114716895A